Noninvasive Brain Stimulation: An Overview of Available Approaches for Research in Neuroaesthetics. (July 2019) - Cattaneo, Zaira
Noninvasive brain stimulation methods, like transcranial magnetic stimulation and transcranial electrical stimulation, are largely employed in cognitive neuroscience to investigate brain–behavior relationships. This review offers an overview of mechanisms of actions of transcranial magnetic stimulation and different types of transcranial electrical stimulation and considers recent studies that have shed light on the neural underpinning of aesthetic evaluation of (visual) artworks by means of noninvasive brain stimulation. Possible future applications of noninvasive brain stimulation for research in neuroaesthetics are also discussed.